Ultimate resistances of member-rotated cold-formed high strength steel tubular T-joints under compression loads. (1st October 2021) - Pandey, Madhup; Young, Ben
Highlights: Cold-formed member-rotated T-joints of S960 steel were tested for static resistances. Chord face failure, combined failure, and chord crown failure modes were observed. Member-rotation had an obvious impact on the joint resistances and load-deformation behaviour of T-joints. Static joint resistances were compared with the design rules available in the literature and EC3. Generally, existing design rules were found not accurate and reliable. Abstract: Brace-rotated and bird-beak joints are novel tubular joint configurations, which are obtained by the rotation of rectangular and/or square hollow section (RHS and/or SHS) members along their respective longitudinal axes by angles corresponding to their cross-sectional diagonal planes. The load vs deformation behaviour and static joint resistances of these novel tubular T-joints are presented in this study. In total, 30 cold-formed high strength steel (CFHSS) member-rotated tubular T-joints were tested. In this paper, member-rotated joints include brace-rotated (BR), square bird-beak (SBB) and diamond bird-beak (DBB) configurations, where RHS and SHS were used as braces and SHS were used as chords. The steel grade of RHS and SHS members was S960. The joint resistances of test specimens were determined by applying axial compression loads through the braces and supporting the chord ends on rollers. The automatic gas metal arc welding process was used to connect braces and chords. The brace width-to-chord width ratio ( β ) ranged from 0.33 to 0.83, effective brace width-to-chord width ratio ( β ′) ranged from 0.25 to 0.88, chord width-to-chord thickness ratio (2 γ ) ranged from 25.3 to 38.9 and brace thickness-to-chord thickness ratio ( τ ) ranged from 0.67 to 1.28. Three failure modes were observed in this investigation, which include chord face failure (F), combined failure (F + W), and chord crown failure (C). The joint resistances were compared with the nominal resistances obtained from the literature and EC3 (2005, [1] ). It has been demonstrated that the design rules available in the literature are generally not suitable for the design of CFHSS brace-rotated and bird-beak T-joints made of S960 steel. Further, the effect of change of member-rotation angle ( ω ) on the joint resistances of CFHSS T-joints made of S960 steel was observed by comparing the joint resistances of BR, SBB and DBB T-joints of this investigation with the joint resistances of traditional RHS T-joints (Pandey and Young (2019), [2] ) made of identical tubular member dimensions and steel grade.